2021
DOI: 10.3390/cancers13102297
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the NLRP3 Inflammasome as a New Therapeutic Option for Overcoming Cancer

Abstract: Inflammasomes are multiprotein complexes that regulate the maturation and secretion of the proinflammatory cytokines interleukin-1beta (IL-1βand interleukin-18 (IL-18) in response to various intracellular stimuli. As a member of the inflammasomes family, NLRP3 is the most studied and best characterized inflammasome and has been shown to be involved in several pathologies. Recent findings have made it increasingly apparent that the NLRP3 inflammasome may also play a central role in tumorigenesis, and it has att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 193 publications
(247 reference statements)
1
50
0
Order By: Relevance
“…Furthermore, riluzole/troriluzole treatment may induce DNA damage, promoting mutagenesis, thereby making mGluR1 tumor cells more immunogenic and responsive to immunotherapy agents. Various reports have shown that the NLR family pyrin domain containing (NLRP) subfamily member 3 (NLRP3) is the major sensor for intracellular danger signals [166]. Activation of NLRP3 by cellular stress results in inflammasome activation catalyzing the formation of proinflammatory cytokines, interleukin IL-1β and IL-18 [166,167].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, riluzole/troriluzole treatment may induce DNA damage, promoting mutagenesis, thereby making mGluR1 tumor cells more immunogenic and responsive to immunotherapy agents. Various reports have shown that the NLR family pyrin domain containing (NLRP) subfamily member 3 (NLRP3) is the major sensor for intracellular danger signals [166]. Activation of NLRP3 by cellular stress results in inflammasome activation catalyzing the formation of proinflammatory cytokines, interleukin IL-1β and IL-18 [166,167].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Various reports have shown that the NLR family pyrin domain containing (NLRP) subfamily member 3 (NLRP3) is the major sensor for intracellular danger signals [166]. Activation of NLRP3 by cellular stress results in inflammasome activation catalyzing the formation of proinflammatory cytokines, interleukin IL-1β and IL-18 [166,167]. Inflammasomes are upregulated in melanomas and NLRP3 expression and activity increases as Various reports have shown that the NLR family pyrin domain containing (NLRP) subfamily member 3 (NLRP3) is the major sensor for intracellular danger signals [166].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The NLRP3 inflammasome has been implicated in promoting the progression of several malignancies by influencing the intrinsic invasiveness of the tumor while also promoting the process of epithelial-mesenchymal transition (EMT) [11][12][13][14][15][16][17][18][19][20]. Indeed, NLRP3 has been shown to be overexpressed by many cancers, while elevated levels of tumor NLRP3 expression have also been associated with an inferior clinical prognosis [15,[21][22][23].…”
Section: Nlrp3 In Cancermentioning
confidence: 99%
“…In response to various intracellular stimuli, NLRs are activated, inducing the assembly of multiprotein complexes known as inflammasomes [7]. As a member of the inflammasome family, NOD-like receptor family pyrin domain containing 3 (NLRP3) is the most studied and best characterized inflammasome, and has been shown to be involved in several pathologies, including neurodegenerative diseases, atherosclerosis, and cancer [7,8]. The NLRP3 inflammasome, through apoptosis-associated speck-like protein (ASC), an adapter protein, activates caspase-1, which in turn promotes the release of pro-inflammatory cytokines interleukin (IL)-1β and IL-18, contributing to the innate immune response [8].…”
Section: Introductionmentioning
confidence: 99%
“…The NLRP3 inflammasome, through apoptosis-associated speck-like protein (ASC), an adapter protein, activates caspase-1, which in turn promotes the release of pro-inflammatory cytokines interleukin (IL)-1β and IL-18, contributing to the innate immune response [8]. However, excessive and aberrant NLRP3 inflammasome activation may lead to cancer progression [8].…”
Section: Introductionmentioning
confidence: 99%